2018
DOI: 10.1155/2018/1691428
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis sativa L. and Nonpsychoactive Cannabinoids: Their Chemistry and Role against Oxidative Stress, Inflammation, and Cancer

Abstract: In the last decades, a lot of attention has been paid to the compounds present in medicinal Cannabis sativa L., such as Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD), and their effects on inflammation and cancer-related pain. The National Cancer Institute (NCI) currently recognizes medicinal C. sativa as an effective treatment for providing relief in a number of symptoms associated with cancer, including pain, loss of appetite, nausea and vomiting, and anxiety. Several studies have described CBD as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
274
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(289 citation statements)
references
References 135 publications
1
274
0
14
Order By: Relevance
“…Relatively recently, multidirectional biological effects have been demonstrated in various preclinical models, including the antioxidant and anti-inflammatory effects of cannabidiol [14,73]. In the context of the above data, CBD seems to be more preferred than other compounds from the phytocannabinoid group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively recently, multidirectional biological effects have been demonstrated in various preclinical models, including the antioxidant and anti-inflammatory effects of cannabidiol [14,73]. In the context of the above data, CBD seems to be more preferred than other compounds from the phytocannabinoid group.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that CBD can also affect redox balance and inflammation by modulating mammalian transient receptor potential (TRP) channels [72,73]. CBD activates vanilloid receptors (TRPV), directly or indirectly, by increasing the level of endogenous AEA, which is one of the endogenous TRPV1 agonists [64].…”
Section: Trp Receptorsmentioning
confidence: 99%
“…Cannabinoids are constituents of cannabis, of which tetrahydrocannabinol (THC) and cannabidiol (CBD) are the most studied so far [4]. While THC, due to its psychoactive properties, has given marijuana a bad name by encouraging its consumption for recreational purposes, CBD lacks such effects [5]. However both cannabinoids are currently commercialized as medicinal products (ex.…”
Section: Introductionmentioning
confidence: 99%
“…inactivation by CBD, a crucial point for crosstalk in the IL-1β-and CBD-induced pathways, 6D cells could undergo reversion to an epithelial phenotype. The acidic precursor of CBD (cannabidiolic acid, CBDA) has been able to inhibit the migration of breast cancer cells and to downregulate the proto-oncogene c-fos and the cyclooxygenase-2 (COX-2), highlighting the possibility that CBDA might act on a common pathway of inflammation and cancer mechanisms [27]. Here, we demonstrated this association, for the first time, between CBD and the inflammatory IL-1β/IL-1R/β-catenin pathway through CB1 activation.…”
Section: Discussionmentioning
confidence: 99%